A framework to support online collaboration in multi-criteria decision processes - Jorge Augusto Pessatto Mondadori (2015)
Multi-criteria problems usually have many uncertainties involved. To help the treatment of these problems, it can be initiated with problem structuring methods, and its solution can be aided by methods of decision analysis. This work proposes a framework with guidelines on how decision-makers, together with a facilitator, can virtually structure and solve a problem collaboratively. The chosen method for problem structuring was Value Focused Thinking and Brainstorming (specifically, VFT and VFB). To analyze the problem and obtain the solution it was used the method of the analytical hierarchical process (specifically, AHP). The framework also considers sensitivity analysis and the discussion of the final decision. To evaluate the proposal, a prototype (in this case an online application) was developed and an empirical application was executed. The application involved decision makers participating actively in the food and beverage industries, in the region of SENAI Toledo Institute of Technology in western Paraná. The problem at hand was to identify services in energy efficiency as a priority in these industries. As a result of empirical evaluation, decision makers have reported the benefits of framework proposed in this work compared to the decision-making processes in which they have been involved previously.